Analisis Teknik Visualisasi Budaya Lokal Medan Dalam Film Sang Prawira (2019) Sutradara Ponti Gea - Dheviyani Dheviyani; Dani Manesah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
The purpose of this article is to find out what cinematographic techniques are used in the movie entitled Sang Prawira by Ponti Gea with cinematographic techniques.This research uses qualitative descriptive research method. In this research, the researcher describes or constructs the theory that exists in the research subject. In this study, the aim is to know, the object of research is to analyze the cinematographic techniques used in the film Sang Prawira by Ponti Gea. The results of the research presented in this article show that cinematographic techniques are analyzed with the 5C camera angle formula, close-up/shot size, composition, continuity and cutting. There are 5 cinematographic techniques of Joseph V. Mascelli A.S.C which is also done by the MRG Film Team in the making of the movie sang prawira, namely camera angle, close up/shot size, composition, continuity, and cutting/editing.